Curious minds not welcome here - Editors (New Zealand Science Review, 2015)
​The New Zealand Association of Scientists (NZAS) is disturbed by news that a large number of scientists at AgResearch, the Crown Research Institute that specialises in the science that supports the agricultural sector, are facing redundancy. “By discarding scientific expertise that has taken the country decades to build just because it no longer meets short-term needs,” said NZAS President, Dr Nicola Gaston, “the government is telling young New Zealanders that careers in science are not for them.” “Inflation has been eating away at the Crown Research Institutes’ core funding for a number of years now,” said Dr Gaston. “CRI scientists are being expected to deliver cutting edge science in support of a growing suite of new government initiatives, but core funding to support salaries and infrastructure has been stagnant for years.” AgResearch’s revenue and staffing have been volatile for the last 5 years. Between 2010 and 2014, AgResearch’s revenues fell by 7% in real terms, with a dramatic decline in revenue of $5m in its last reporting period. Furthermore, figures tabled at the Education and Science Select Committee earlier this year show that 53% of staff at AgResearch have worked there less than two years. “This is a deeply concerning level of staff turnover for any organisation, let alone a science agency engaged in long-term research programmes which require continuity and stable working conditions,” said Dr Gaston. “One has to question the likelihood of success of any restructuring plan that will cause further uncertainty.” The New Zealand Association of Scientists (www.scientists.org.nz) is a nationwide association of practising research scientists spanning the universities, technical institutes, Crown Research Institutes, government departments, industry, museums, other science institutions, and independent researchers.